Campaign Design For Plastic Waste Treatment Workshop In Bandung City - Magfirah Nugraheni, Andi; Widiatmoko Soewardikoen, Didit; Azhar, Hanif; Nur Hadiansyah, Mahendra (Advances In Social Humanities Research, 2024)
This research is entitled "Campaign Design for a Plastic Waste Processing Workshop in Bandung City". This research focuses on Olah Plastic, a business entity in Bandung City, which processes and recycles plastic waste. The study focuses on designing a digital campaign to enhance students' understanding and awareness of plastic waste processing. This design aims to produce design media in the form of a digital campaign so that it can attract students to be more aware of plastic waste processing. The design employs a design thinking method, including Empathize, Define, Ideate, Prototype, and Test, with a design approach. The data collection process involved literature studies, observations, and interviews. The research aimed to design a digital poster for social media accessibility for students. The poster that has been designed is also made in the form of a design mockup so that it can illustrate how the final product will look, giving the client a clear picture of the design.